Perancangan Aplikasi (App) Buku Digital Sri Pohaci untuk Anak Pra-Sekolah: Pengenalan Sembilan Tanaman Pangan Pokok - Citra Remi; Priyanto Sunarto; Riama Maslan (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2013)
Folktales need to be modified and packaged in a variety of media to preserve classic literature. The myth of Sundanese goddess of rice, Sri Pohaci is modified to fit the current context, without changing the basic structure of the story. As the story told, Sri Pohaci incarnated into nine plants. These plants are modified to nine consumptive plants, to support diversification of food consumption program through the story of Sri Pohaci, intended for pre-school children. The pre-design phase for this research applies qualitative methodology based on action research. The e-book application (app) design utilizes digital storytelling method, combined with touch-screen technology to enable interactive animated features. The concept of storytelling through narration, visual, audio and interactivity can increase the sensation of two-way interaction to encourage children's comprehension and enjoyment of storybook.